Diplotriaena obtusa (Nematoda: Filariidae) infection in first-year Sylvia atricapilla from Poland – molecular evidence. Issue 1 (1st January 2021) - Stanicka, A.; Zając, K. S.; Jefimow, M.; Wojciechowski, M. S.
Abstract: Insectivorous birds are particularly vulnerable to nematodes with heteroxenous life cycles. Although there are many studies on bird filarioids, they mainly focus on economically important or pet bird species, and as a result, the species diversity of these parasites is insufficiently studied. Research on the genus Diplotriaena and their hosts is neglected, although they are globally occurring and dangerous parasites with low specificity to the final host. Here we report the prevalence, invasive intensity and species affiliation of the filarial nematodes of the genus Diplotriaena in a common passerine – Eurasian blackcap ( Sylvia atricapilla, L.). In total, 24 first-year individuals of S. atricapilla were caught in Toruń (central Poland) at their breeding grounds in July and August 2019, and after 7 months in captivity, they were killed and dissected. Over 20% of dissected birds were infected with Diplotriaena, and their air sacs were inhabited by 1 to 18 adult worms. Molecular identification of nematode worms was done using the 18S small subunit rRNA gene, and they were identified as D. obtusa . Our study is the first to show the molecular confirmation of the presence of D. obtusa in S. atricapilla .